ANALISIS KINERJA PROSES LATEX DIPPING MENGGUNAKAN TEKNIK CAPABILITY PROCESS (STUDI KASUS: PT DHARMA MEDIPRO) - Maimury, Yona; Tannady, Hendy (Jurnal Ilmiah Teknik Industri, 2015)
The quality of product is reflected from the performance of its process. The most frequent issue that occurs in local company today -- is -- most company only focuses on the output regardless the process. It causes the difficulty that occurs in local company to compete with other company in global environment. One of the local companies that has their business shifting up significantly, with the great number of export target and actual export, is PT Dharma Medipro, which has many processes on the production of sphygmomanometer. One of the processes that critical to quality is latex dipping process, where the yield of this process that must be considered is the thickness of the bag component. In order to improve the process, we should first establish the measurement of process performance using capability process technique, which is one of the tools came from statistical process control method. The result indicates that the process is unstable with the value of capability indices Cp = 4,69 ; Cpk = -0,77 ; Cpu = -0,77 ; Cpl = 10,15 ; and Cpm = 0,28, moreover the number of part per million (PPM) that out of the spesification limit reach 912.500 units.